Man’s Continuous Search for Salvation in Beckett’s plays: From Arrival in Waiting For Godot to Departure in Endgame - Hussein, Marwa Sami; Abdullah, Ansam Riyadh; Jasim, Alaa Hameed (Journal of Tikrit University for Humanities, 2021)
Following an existential point of view, the absurd theatre depicts ideas that seem to have illogical explanation. As a case in point, Samuel Beckett is the most eminent of the absurdist playwrights, in a sense that he deals with the dullness of routine, the futility of human action, and humans’ inability to communicate. Beckett who has experienced so much of life became a man with a prophetic vision, and the creator of new concepts of modern theatre. His journey continues after writing Waiting for Godot to write Endgame. Both plays share the same view that man is living in a world without a clue and placing in a universe with no purpose. This study provides a framework of Beckett’s two absurd plays Waiting for Godot and Endgame elucidated under the umbrella of both existentialism and absurd theatre. It is divided into two sections and a conclusion. Section one deals with the genre of these two plays and the philosophy of existentialism which has its effect on the writings of the modern age. Also, it explains the main features of the absurd theatre and how the modern tragi-comedy is used synonymously with absurd theatre. Section two deals with the game of waiting in Waiting for Godot, and the final stage of life in Endgame, and how Endgame is depicted as the third act of Wating for Godot. It also shows the idea of seeking salvation which dominates the two plays but in different ways. The last part of this study is the conclusion which sums up the findings of the study.